1997
DOI: 10.1093/emboj/16.14.4467
|View full text |Cite
|
Sign up to set email alerts
|

MutS mediates heteroduplex loop formation by a translocation mechanism

Abstract: Interaction of Escherichia coli MutS and MutL with heteroduplex DNA has been visualized by electron microscopy. In a reaction dependent on ATP hydrolysis, complexes between a MutS dimer and a DNA heteroduplex are converted to protein‐stabilized, α‐shaped loop structures with the mismatch in most cases located within the DNA loop. Loop formation depends on ATP hydrolysis and loop size increases linearly with time at a rate of 370 base pairs/min in phosphate buffer and about 10 000 base pairs/min in the HEPES bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
279
2
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(297 citation statements)
references
References 32 publications
15
279
2
1
Order By: Relevance
“…5A, the maximum level of binding of MutS to the heteroduplex GG/CT is much higher as compared with that of the perfectly paired duplex, as expected for a mismatch binding protein. As deduced at saturation binding obtained at a higher protein concentration (RU max ϭ 650, data not shown), MutS as a dimer was found to bind to the heteroduplex in a 1:1 manner, in agreement with previous studies (40,49). Adding a cisplatin 1,2-intrastrand adduct to the GG/CC homoduplex results in an increase of the plateau level.…”
Section: Muts Recognizes An Extensive Set Of Cisplatin 12-intrastransupporting
confidence: 90%
“…5A, the maximum level of binding of MutS to the heteroduplex GG/CT is much higher as compared with that of the perfectly paired duplex, as expected for a mismatch binding protein. As deduced at saturation binding obtained at a higher protein concentration (RU max ϭ 650, data not shown), MutS as a dimer was found to bind to the heteroduplex in a 1:1 manner, in agreement with previous studies (40,49). Adding a cisplatin 1,2-intrastrand adduct to the GG/CC homoduplex results in an increase of the plateau level.…”
Section: Muts Recognizes An Extensive Set Of Cisplatin 12-intrastransupporting
confidence: 90%
“…The heteroduplexes used in these experiments contain an NheI site 5 bp from the mismatch, which is rendered resistant to cleavage by MutS binding (12). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One invokes movement of MutS or the MutL-MutS complex along the helix between the mismatch and the strand signal (11)(12)(13), a second posits mismatch recognition by MutS as a trigger for polymerization of a second protein along the helix between the two DNA sites (11), and the third attributes interaction of the two sites to a DNA-looping mechanism (14,15). Several laboratories have demonstrated that, when challenged with ATP, MutS homologs leave a mismatch by movement along the helix contour, and evidence for movement of the MutL-MutS homolog complex along DNA also is available (reviewed in refs.…”
mentioning
confidence: 99%
“…Several research groups have reported an apparent reduction in the affinity of MutS for mismatched DNA following ATP binding, which manifests as MutS sliding off short linear mismatched DNA substrates with unblocked ends during gel mobility-shift analysis (1,13,(23)(24)(25)28,48); presumably, such movement of MutS on DNA serves an important function during mismatch repair. Since we have now identified some nucleotide-bound forms of MutS in the pathway, we tested their interaction with +T-containing duplex DNA substrate.…”
Section: What Is Their Function?mentioning
confidence: 99%